Demethylase FTO mediates m6A modification of ENST00000619282 to promote apoptosis escape in rheumatoid arthritis and the intervention effect of Xinfeng Capsule - Wang, Fanfan; Wen, Jianting; Liu, Jian; Xin, Ling; Fang, Yanyan; Sun, Yue; He, Mingyu (Frontiers in Immunology, 2025)
IntroductionThe pathological mechanisms of rheumatoid arthritis (RA) are closely associated with the apoptosis escape of fibroblast-like synoviocytes (FLS). The m6A modification of long non-coding RNAs (lncRNAs) plays a critical regulatory role in RA pathogenesis. Xinfeng Capsule (XFC), a clinically effective traditional Chinese medicine formulation, has been shown to alleviate RA by inhibiting FLS apoptosis escape. However, its molecular mechanisms remain unclear. This study aimed to elucidate the mechanism by which the demethylase FTO promoted FLS apoptosis escape through the m6A modification of lncRNA ENST00000619282 and to reveal the therapeutic targets of XFC in treating RA by intervening in this m6A-dependent pathway.MethodsA retrospective analysis was conducted on 1603 RA patients using association rule mining and random walk algorithms to evaluate the efficacy of XFC. The proliferation and apoptosis of co-cultured RA-FLS were assessed using CCK-8, flow cytometry (FCM), and molecular biology techniques. Bioinformatics prediction, MeRIP-qPCR, RIP, and RNA pull-down assays were employed to identify the m6A modification sites of ENST00000619282 and their interactions with FTO/YTHDF1. Additionally, FISH, luciferase reporter assays, and rescue experiments were performed to validate the regulatory role of ENST00000619282 and its sponge-like function in RA-FLS. Clinical samples were analyzed to determine the correlation between FTO/YTHDF1/ENST00000619282/Bax/Bcl-2 and immune-inflammatory markers. Furthermore, the binding affinity of XFC active components to NF-κB was assessed through molecular docking.ResultsRetrospective data mining demonstrated that XFC significantly improved immune-inflammatory markers in RA patients. Mechanistically, FTO reduced the m6A modification level of ENST00000619282, enhancing its stability and promoting YTHDF1-dependent expression, which in turn inhibited PUF60 and activated the NF-κB pathway, ultimately leading to FLS apoptosis escape. XFC downregulated FTO, increased the m6A modification of ENST00000619282, blocked the NF-κB signaling, inhibited RA-FLS proliferation, as well as induced their apoptosis. Clinical validation revealed that FTO/YTHDF1/ENST00000619282/Bax/Bcl-2 was closely associated with immune-inflammatory markers in RA patients. After XFC treatment, FTO, ENST00000619282, and Bcl-2 expressions were decreased, while YTHDF1 and Bax expressions were increased (all P<0.05). Molecular docking confirmed that the active components of XFC (calycosin-7-O-beta-D-glucoside, calycosin, and formononetin) exhibited strong binding affinity to NF-κB p65.ConclusionFTO promoted FLS apoptosis escape and RA progression by activating the NF-κB pathway through the m6A-dependent ENST00000619282/YTHDF1 axis. XFC inhibited this pathway by modulating FTO-mediated m6A modification, providing a novel RNA epigenetic regulatory strategy for RA treatment.